2017
DOI: 10.1016/j.sleep.2017.11.462
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality in university students with premenstrual dysphoric disorder

Abstract: •Original research article• Background: Up to 8% of women in their reproductive years are affected by Premenstral Dysphoric Disorder (PMDD). Sleep disturbances such as insomnia or hypersomnia are one of the DSM-IV-TR's defining criteria for the diagnosis of PMDD and are found in about 70% of women with the disorder. However, studies are lacking that specifically address the effects of PMDD on quality of sleep. Aim: This study was designed to evaluate the prevalence of Premenstrual DysphoricDisorder (PMDD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Cheng et al 27 in a study of 677 university students determined that PMS was associated with poor sleep quality. A study by Khazaie et al 38 identified that 80.5% of students in the premenstrual dysphoric disorder (PMDD) group had low sleep quality, while 56.4% of students in the group without PMDD had low sleep quality. They determined that low sleep quality, daily dysfunction and sleep disorder were among common sleep problems in PMDD students.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al 27 in a study of 677 university students determined that PMS was associated with poor sleep quality. A study by Khazaie et al 38 identified that 80.5% of students in the premenstrual dysphoric disorder (PMDD) group had low sleep quality, while 56.4% of students in the group without PMDD had low sleep quality. They determined that low sleep quality, daily dysfunction and sleep disorder were among common sleep problems in PMDD students.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that women with premenstrual syndrome (PMS) had poorer sleep quality, a higher perception of unrefreshing sleep, increased total sleep time recorded by polysomnography, a lower saturation of peripheral oxygen, and more subthreshold insomnia [4]. Another study that focused on female university students who experienced PMDD and sleep problems revealed that lower sleep quality, daytime dysfunction, and sleep disturbances were common among such students [5]. Sleep disturbance and decreased melatonin secretion due to hormonal fluctuations during the luteal phase of the menstrual cycle could explain the sleep complaints associated with PMDD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative or quantitative PCR (viral load) was repeated for all patients at the end of treatment and also 12e24 weeks after finishing the treatment to find out the sustained virological response (SVR). Patients were evaluated before the beginning of treatment and 12e24 weeks after finishing their treatment using the Persian translated versions of the Pittsburgh Sleep Quality Index (PSQI) [9], Beck depression inventory questionnaire [10] and SF-36 healthrelated QoL questionnaires [11]. Cirrhosis was confirmed by liver transient elastography (FibroScan).…”
Section: Chronic Hcv-infected Patients Receiving Daas In the Middlementioning
confidence: 99%